Validation of the Parental Facilitation of Mastery Scale – II - Zalta, Alyson K.; Allred, Kelly M.; Jayawickreme, Eranda; Blackie, Laura E.R.; Chambless, Dianne L. (Wiley, 2017)
Objective: To develop a more reliable and comprehensive version of the Parental Facilitation of Mastery Scale (PFMS). Method: In Study 1, 387 undergraduates completed an expanded PFMS (PFMS-II) and measures of parenting, perceived control, responses to early life challenges, and psychopathology. In Study 2, 182 trauma-exposed community participants completed the PFMSII and measures of perceived control, psychopathology, and well-being. Results: In Study 1, exploratory factor analysis of the PFMS-II revealed two factors. These factors replicated in Study 2; one item was removed to achieve measurement invariance across race. The final PFMS-II consisted of a ten-item overprotection scale and a seven-item challenge scale. In both samples, this measure demonstrated good convergent and discriminant validity and was more reliable than the original PFMS. Parental challenge was a unique predictor of perceived control in both samples. Conclusions: The PFMS-II is a valid measure of important parenting behaviors not fully captured in other measures.